Canakinumab for Treatment of Adult-Onset Still's Disease to Achieve Reduction of Arthritic Manifestation (CONSIDER): phase II, randomised, double-blind, placebo-controlled, multicentre, investigator-initiated trial. Issue 8 (13th May 2020) - Kedor, Claudia; Listing, Joachim; Zernicke, Jan; Weiß, Anja; Behrens, Frank; Blank, Norbert; Henes, Joerg Christoph; Kekow, Joern; Rubbert-Roth, Andrea; Schulze-Koops, Hendrik; Seipelt, Eva; Specker, Christof; et al.
Abstract : Background: Inhibition of interleukin (IL)-1 represents a promising treatment option in adult-onset Still's disease (AOSD). Objective: To investigate the efficacy and safety of canakinumab in patients with AOSD and active joint involvement by means of a multicentre, double-blind, randomised, placebo-controlled trial. Methods: Patients with AOSD and active joint involvement (tender and swollen joint counts of ≥4 each) were treated with canakinumab (4 mg/kg, maximum 300 mg subcutaneous every 4 weeks) or placebo. The primary endpoint was the proportion of patients with a clinically relevant reduction in disease activity at week 12 as determined by the change in disease activity score (ΔDAS28>1.2). Results: At enrolment, patients had high active disease with a mean DAS28(ESR) of 5.4 in the canakinumab and 5.3 in the placebo group, respectively. In the intention-to-treat analysis, 12 patients (67%) in the canakinumab group and 7 patients (41%) in the placebo group fulfilled the primary outcome criterion (p=0.18). In the per-protocol analysis, significantly higher American College of Rheumatology (ACR) 30% (61% vs 20%, p=0.033), ACR 50% (50% vs 6.7%, p=0.009) and ACR 70% (28% vs 0%, p=0.049) response rates were observed in the canakinumab group compared with the placebo group. Two patients in the canakinumab group experienced a serious adverse event. Conclusion: Although the study was terminated prematurely and the primary endpoint was not achieved, treatment with canakinumab led to an improvement of several outcome measures in AOSD. The overall safety findings were consistent with the known profile of canakinumab. Thus, our data support indication for IL-1 inhibition with canakinumab in AOSD.